2021
DOI: 10.47197/retos.v42i0.86448
|View full text |Cite
|
Sign up to set email alerts
|

Importancia de la actividad física sobre la inteligencia emocional y diferencias de género (Impact of physical activity on emotional intelligence and sex differences)

Abstract: Los factores emocionales y su desarrollo en contextos donde abunda la práctica deportiva están en el punto de mira de estos últimos años. Esto es así pues la actividad física tiene una estrecha relación con la canalización de las emociones y su efecto en el rendimiento deportivo, así como las diferencias sexuales en la comprensión de estos términos. Por estas razones, la presente investigación presenta como principal objetivo describir el nivel de práctica de actividad física, inteligencia emocional y l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
2
4
0
9
Order By: Relevance
“…In our case, the students that engage in more physical activity present better emotional intelligence and more appropriate coping styles, compared to the undergraduates that do less physical exercise. Other studies have reported similar findings (Acebes-Sánchez et al, 2019;Budnik-Przybylska et al, 2021;López et al, 2021) where high levels of physical activity are associated with better control of the emotions in the two dimensions, highlighting their ability to repair themselves, as well as their emotional clarity. Thus, it is important that university institutions promote engagement in physical activity and sports as a measure of self-care, and to provide health and psychological benefits and avoid a sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In our case, the students that engage in more physical activity present better emotional intelligence and more appropriate coping styles, compared to the undergraduates that do less physical exercise. Other studies have reported similar findings (Acebes-Sánchez et al, 2019;Budnik-Przybylska et al, 2021;López et al, 2021) where high levels of physical activity are associated with better control of the emotions in the two dimensions, highlighting their ability to repair themselves, as well as their emotional clarity. Thus, it is important that university institutions promote engagement in physical activity and sports as a measure of self-care, and to provide health and psychological benefits and avoid a sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 60%
“…Finally, doing sport and engaging in physical activity provides a range of benefits, including physical fitness, mental health, psychological impacts, emotional intelligence, self-esteem, body image and the reduced risk of premature death and chronic diseases (Acebes-Sánchez et al, 2019;Adarve et al, 2019;Alvear-Galindo et al, 2014;Grasdalsmoen et al, 2020;López et al, 2021;Rivas-Espinosa et al, 2019;Sanchis-Soler et al, 2022;Tang et al, 2020). The World Health Organisation (WHO) established the importance of regular physical activity and published the Global Recommendations on physical activity for health in 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siguiendo con el planteamiento de la primera hipótesis, a pesar de que las niñas reportaron ser ligeramente más activas que los niños, estos resultados no fueron estadísticamente significativos. Por lo que, estos hallazgos no permiten corroborar lo que la literatura previa reporta, donde en general, se plantea que los varones son más activos físicamente que las niñas (Aguilar-Farias et al, 2020;Baños et al, 2021;Boente et al, 2021;Castillo et al, 2018;García et al, 2020;Herazo, et al, 2019;López et al, 2021;Rodríguez-Fernández et al, 2018). Esto podría deberse a distintos factores, que pueden ir desde la for-ma en la que se evalúa la propia actividad física, derivada de su definición y/o criterios utilizados, hasta la edad de los niños que han sido evaluados.…”
Section: Discussionunclassified
“…Algunos estudios reportan que los niños realizan más actividad física que las niñas (Aguilar-Farias, Martino-Fuentealba, & Chandia-Poblete, 2020;Baños, Barretos-Ruvalcaba, Baena-Extremera, & Fuentesal-García, 2021;Boente, Leirós-Rodríguez, & García-Soidán, 2021;Castillo, Tornero, & García, 2018;García, et al, 2020;Herazo, et al, 2019;López, Zurita-Ortega, Ubago, & González, 2021;Rodríguez-Fernández, Rico-Díaz, Neira-Martín, & Navarro-Patón, 2021;Zurita-Ortega et al, 2018). Sin embargo, Marambio et al (2020) indican que las niñas practican más actividad física entre semana que en fin de semana.…”
Section: Introductionunclassified